Influence of the use of mooring line pretension on the behaviour of a moored oil tanker - Paulo Jorge Rosa-Santos (2009)
The influence of an increase of the breast lines pretension on the behavior of an oil tanker moored at the Berth "A" of the Leixões Oil Terminal, Porto, Portugal,is analyzed in the paper, for two water levels, based on the results of a physical model study. Numerical model results obtained for some test conditions are also presented, as well as a brief description of the local environmental conditions and the existing operational conditions at that oil terminal. Furthermore, a stereoscopic vision system that is being developed to measure the motions of ships moored at the oil terminal (prototype) is described and some results of the preliminary tests of the equipment in the laboratory environment are presented.Keywords: mooring line pretension; moored ship behavior; oil terminal; physical modeling; numerical modeling; prototype measurements.